PRINSIP IKTIKAD BAIK DALAM KONTRAK PENGADAAN VAKSIN SEBELUM ADANYA HASIL UJI KLINIS - Adibah Kultsum (2022)
In early 2020, the world was electrified with the advent of the Corona Virus or Corona Virus Disease 2019 (COVID-19). The spread of this virus began in Wuhan, China at the end of 2019. According to World Health Organization data, WHO on March 1, 2020, the virus has spread rapidly to 65 countries around the world. Given that the virus is a new type of virus, information related to the virus is also limited, and is still under research. The effectiveness of treatments that can prevent the spread of COVID-19, as well as vaccines and drugs that effectively cure COVID-19 patients is still uncertain. The government is carrying out a vaccine procurement contract to overcome the COVID-19 disaster which is carried out through an emergency procurement of goods (PBJ) procedures. The method used in this study uses a normative legal research method conducted by examining library materials or secondary data with a statutory approach or statute approach. The results of the study show that Article 27 paragraph (2) and paragraph (3) of the COVID-19 Handling Act which has true legal impunity does not necessarily eliminate the responsibility of procurement actors but rather procurement actors are still subject to legal liability based on good parameters and implementation in accordance with statutory regulations. An important conclusion from this study is the principle of good faith in the procurement of vaccines for which no clinical trial results are absolutely necessary for the parties especially the government because the government is obliged to be accountable for public health and safety. Keywords : Good Faith, Procurement of Good/Services, Covid-19